2014
DOI: 10.1002/2013jd020378
|View full text |Cite
|
Sign up to set email alerts
|

Data processing procedure using distribution of slopes of phase differences for broadband VHF interferometer

Abstract: The upgraded VHF digital interferometer (VHF DITF) system is introduced which can continuously sample the radiation associated with lightning. A new processing technique was implemented which uses the distribution of slopes of the phase difference versus frequency to locate the radiation source. By using this technique, frequency components which are not due to lightning can be excluded and low as well as high amplitude sources are located. As a result, both positive breakdown and negative breakdown are locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 30 publications
3
28
0
Order By: Relevance
“…Detailed and thorough interferometric investigation of spatial and temporal development of lightning discharges have been reported previously in a number of studies (e.g., Akita et al, ; Rhodes et al, ; Rison et al, ; Shao & Krehbiel, ; Shao et al, ; Stock et al, ). In this paper, we present example observations with the Los Alamos BIMAP system to demonstrate the new capability of the system and to report some new physics insights for some of the discharge processes in the 6 June 2017 IC flash (Figure ).…”
Section: Observation Resultsmentioning
confidence: 91%
“…Detailed and thorough interferometric investigation of spatial and temporal development of lightning discharges have been reported previously in a number of studies (e.g., Akita et al, ; Rhodes et al, ; Rison et al, ; Shao & Krehbiel, ; Shao et al, ; Stock et al, ). In this paper, we present example observations with the Los Alamos BIMAP system to demonstrate the new capability of the system and to report some new physics insights for some of the discharge processes in the 6 June 2017 IC flash (Figure ).…”
Section: Observation Resultsmentioning
confidence: 91%
“…Comparing positive and negative breakdown in lightning discharges, Williams [] indicated that positive breakdown involves much weaker radiation than negative breakdown. We presume that positive breakdown also involves remarkably weaker radiation in LF band than negative breakdown from VHF and UHF lightning observation results [ Shao et al ., ; Kawasaki et al ., ; Akita et al ., ; Stock et al ., ]. Therefore, we speculate that most of sporadic BOLT sources located in the NCR are not source locations associated with positive breakdown; instead, each source location is one part of recoil negative leaders that propagated along the same channel where previous positive leaders propagated, although no clear channel of the recoil leader is imaged in this event.…”
Section: Flashes Mapped By Boltmentioning
confidence: 99%
“…BOLT sources associated with recoil negative leaders moved away from the initiation source location of the IC with time at an almost constant altitude of 6 km. Taking into account that lightning discharges propagate as a bidirectional tree [ Mazur and Ruhnke , ; Kawasaki et al ., ; Akita et al ., ; Stock et al ., ], it is likely that undetectable positive leader developed horizontally at about 6 km altitude from the initiation point of this flash. It appears that the positive leader at least had two branches.…”
Section: Flashes Mapped By Boltmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Because a lightning leader develops bidirectionally [25,26], positive leaders might have developed in the opposite direction of the negative leader. In this event, a positive leader might have developed below the initiation point.…”
Section: An Ic Dischargementioning
confidence: 99%